2017
DOI: 10.21873/anticanres.11948
|View full text |Cite
|
Sign up to set email alerts
|

Risk-reducing Salpingo–Oophorectomy in Women at Higher Risk of Ovarian and Breast Cancer: A Single Institution Prospective Series

Abstract: Our study, covering an 18-year period, shows a substantial low risk of occult cancer among a high-risk population of women undergoing RRSO. Our data still support the indication for RRSO in higher-risk patients. An endometrial biopsy should also be routinely obtained as it raises the chances of detecting occult endometrial cancers that may be otherwise missed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
6
1
Order By: Relevance
“…According to the available literature, the prevalence of occult cancer found after RRSO varies from 2% to 17%. [13][14][15][16][17][18][19][20][21][22]28 In our study, the prevalence of occult cancer in BRCA1/2 positive women was 5.5%, which is similar to what Conner et al have found. 29 We detected fewer occult cancers than Powell et al who reported a rate of 7.9% and more than Reitsma et al (2.2%) and Finch et al (4.2%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to the available literature, the prevalence of occult cancer found after RRSO varies from 2% to 17%. [13][14][15][16][17][18][19][20][21][22]28 In our study, the prevalence of occult cancer in BRCA1/2 positive women was 5.5%, which is similar to what Conner et al have found. 29 We detected fewer occult cancers than Powell et al who reported a rate of 7.9% and more than Reitsma et al (2.2%) and Finch et al (4.2%).…”
Section: Discussionsupporting
confidence: 91%
“…Occult cancers have been reported to occur between 2% and 17% and STICs between 3% and 12%, respectively. [13][14][15][16][17][18][19][20][21][22] The occult cancer detection is probably influenced by the age at RRSO, gynaecological screening prior to RRSO, extent of the surgical removal of specimens and the accuracy of tubal pathohistological assessment. It is known that the protocol for sectioning and extensively examining the fimbriated end of the Fallopian tube (SEE-FIM) enables a more exact histopathological examination of the distal tube with its fimbrial part.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, all the biopsies we performed in patients diagnosed with STIC as well as invasive cancers were negative for the presence of neoplastic cells, suggesting that peritoneal staging might be a surgical overtreatment. It should be underlined that we found a low rate of STIC compared with other previously reported [20] albeit the Sectioning and Extensively Examining the Fimbriated End Protocol was applied [21], but other papers describe the same percentage [15,16,20]; additionally, the median age of our study population is lower than that reported in those cases with higher STIC rates.…”
Section: Discussioncontrasting
confidence: 66%
“…Nonetheless, the incidence of occult malignancies or STIC reported in the literature is highly variable and is influenced by several factors, including patients' age at surgery, adequacy of preoperative work-up and accuracy of histopathological examination [15,16]. Moreover, there is heterogeneity in study design: most of them are retrospective and without standardization of the surgical and pathological procedures [17,18]; furthermore, some studies include both BRCA mutation carriers and wild-type BRCA patients at high risk based on family or personal history.…”
Section: Introductionmentioning
confidence: 99%
“…P53 signatures are reported on by six studies, with an estimated incidence of 16.2% (95% CI, 2.2-39.7) [16,20,25,27,40,47]. Finally, STIL was reported on by six studies and has an estimated incidence of 1.6% (95% CI, 0.3-3.8) [16,26,27,44,47,55].…”
Section: Study Characteristicsmentioning
confidence: 98%